DARI TEOLOGI KE MASALAH SOSIAL: RELEVANSI GAGASAN ’RELIGIOUS PROBLEMS’ IVAN STRENSKI BAGI ANALISIS KONFLIK DAN PENGEMBANGAN MASYARAKAT - Muhibuddin; Dody S. Truna; Rifki Rosyad (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2025)
This article critically examines Ivan Strenski’s work “The Proper Object of the Study of Religion: Why It Is Better to Know Some of the Questions Than All of the Answers”, which positions “problems of religion” as the epistemological foundation of religious studies. Using a qualitative approach through library research, this study analyzes Strenski’s argument that religious inquiry should focus on fundamental questions emerging from religious phenomena, rather than defining what religion is. The analysis reveals that Strenski successfully offers an important epistemological repositioning for religious studies to remain scientific while avoiding both theologization and cultural reductionism. However, his concept remains normative and lacks an operational methodology for empirical application. This review highlights the significance of Strenski’s ideas in enriching the epistemological discourse of religious studies and underscores the need for a more concrete methodological framework to implement his theoretical propositions.